A Novel Entry to 3,4,5-Trisubstituted 2-Pyrrolidones from Isoxazoline-N-oxides - Zhmurov, Petr A.; Ushakov, Pavel Yu.; Novikov, Roman A.; Sukhorukov, Alexey Yu.; Ioffe, Sema L. (Synlett, 2018)
A novel strategy for the synthesis of stereochemically defined 3,4,5-trisubstituted 2-pyrrolidones was developed. The suggested approach involves reductive domino-type recyclization of 3-aminomethyl-substituted isoxazolines as a key stage. The latter are prepared via α-C–H functionalization of readily available isoxazoline-N-oxides.
Keywords: 2-pyrrolidones; isoxazolines; reduction; C–H functionalization; azides